2013
DOI: 10.1136/annrheumdis-2012-eular.634
|View full text |Cite
|
Sign up to set email alerts
|

AB0634 Chinese experience with tripterygium wilfordii multiglycoside as long-term maintenance therapy in lupus nephritis

Abstract: Background Mycophenolate mofetil (MMF) and azathioprine (Aza) has long been used as maintenance immunosuppressive treatment for lupus nephritis. However, the benefits of MMF was limited by its high cost in China. Unpredictable severe pancytopenia induced by Aza is not common but may be fetal. Optimal therapeutic modalities with more cost-effectiveness and safety were required to be identified and thus modify the immunotherapeutic strategies. Tripterygium wilfordii multiglycoside (GTW), an authorized Chinese pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Modern pharmacological studies have supported the anti-inflammatory and antitumor effects of TG, which is widely used in the clinical treatment of RA and nephrotic syndrome [ 15 , 16 ]. TG has been reported to exert anti-inflammatory effects [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern pharmacological studies have supported the anti-inflammatory and antitumor effects of TG, which is widely used in the clinical treatment of RA and nephrotic syndrome [ 15 , 16 ]. TG has been reported to exert anti-inflammatory effects [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tripterygium glycosides (TGs) are nonsteroidal immunosuppressants. Physiological activities are attributed to diterpene lactone alkaloids and triterpenes that were reported to exert anti-inflammatory, antitumor and immunosuppressive effects [15][16][17][18] and were shown to protect the nervous system [19]. Recent researchers have reported that TG ameliorates inflammation in astrocytes induced by lipopolysaccharide (LPS) by decreasing the expression of TNF-α, iNOS and IL6 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of new drugs or methods is required to treat the symptoms of AD. Tripterygium glycoside (TG) is extracted from the roots of Tripterygium wilfordii Hook.f, and has been shown to protect against rheumatoid arthritis (RA), 4 lupus nephritis (LN), 5 diabetes mellitus (DM), 6 and Guillain-Barre syndrome (GBS). 7 Animal experiments showed that TG has protective effects on the central nervous system.…”
Section: Introductionmentioning
confidence: 99%